Turbo pascal 7.0 - Savitch, Walter J. (Redwood City, California : Benjamin Cummings, 1993)
The new edition of Walter Savitch's Turbo Pascal, 7.0 opens the door to a powerful new programming environment--Turbo Pascal 7.0! Based on the recently-released compiler from Borland, Savitch's Fourth Edition combines a modern approach to computer science and programming with up-to-date coverage of the new Turbo Pascal 7.0 environment. In this new edition, you'll find an emphasis on software engineering principles, early coverage of units and abstract data types, and a comprehensive chapter on algorithm efficiency including Big "O" Notation. In addition, the text provides an optional chapter on object-oriented programming for instructors who wish to introduce their students to this advanced programming approach.
Introduction to Computers and the Turbo Environment. Introduction to Algorithms and Pascal. More Pascal and an Introduction to Software Engineering. Procedures and Top-Down Design. Modularity, Functions, and Data Flow. Designing Programs that Make Choices. Design and Implementation of Loops. Units and Abstract Data Types. One-Dimensional Arrays and Strings. Complex Array Algorithms and Complex Array Structures. Records and Other Data Structures. Files and Secondary Storage. Recursion. Numeric Computations and Random Number Generators. Sorting, Searching, and the Analysis of Algorithms. Pointers and Dynamic Data Structures. Object-Oriented Programming.
Includes bibliographical references and index.
Keywords: PASCAL (COMPUTER PROGRAM LANGUAGE)